PERLINDUNGAN HUKUM BAGI KREDITUR DALAM PERJANJIAN FIDUSIA - Nurmelinda, Moya (Yustitia, 2021)
Fiduciary is the transfer of ownership rights to an object on the basis of trust provided that the object whose ownership rights are transferred remains in the control of the owner of the object. While the Fiduciary guarantee in accordance with Article 1 paragraph 2 of Law no. 42 of 1999 is a security right on a movable object, both tangible and intangible and immovable objects, especially buildings that cannot be encumbered with mortgage rights. Research Methods in this scientific papers using normative juridical research methods. As well as using data collection techniques carried out using descriptive analysis techniques, with secondary data sources, which include primary legal materials such as laws and regulations relating to fiduciary and mortgage rights. The results in this research can beexplained that as referred to in Act No. 4 of 1996 concerning Mortgage Rights which remains in the control of the fiduciary, as collateral for the repayment of certain debts and gives priority to other creditors. Fiduciary guarantees can be carried out and stipulated in afiduciary certificate which is authorized by a notary. With this certificate, it can also be used as a protection for both parties, both as a borrower and as a lender, no one is harmed.